Penerapan Komputerisasi Akuntansi dan Kebutuhan di Era Digital pada Yayasan Peduli Tali Bangsa - Dian Widiyati; Fitriyah Fitriyah; Neneng Hasanah; Agus Afandi; Andry Sugeng (Abdimisi, 2021)
The development of information technology is growing rapidly every day so that the need for information is becoming increasingly important and increasingly needed in connection with the purpose of information, namely to produce something more meaningful and useful for making a fast and accurate decision. Of the many programs for preparing financial reports, the most widely used is the Microsoft Excel program. Peduli Tali Bangsa Foundation is a foundation that is concerned with the empowerment of human resources for orphans and duafa which has held a series of social activities as well as basic activities for religious education and guidance. This community service activity is carried out at the Peduli Tali Bangsa Foundation which is located at Ruko Aviva No. R3, RT: 02 RW: 01, Kampung Sawah, Ciputat District, South Tangerang City, Banten. The event was carried out in a conducive manner. The implementation began with an opening and then continued with the delivery of remarks from the chairman of Community Service (PKM) and representatives from the Foundation. The purpose of this activity is to help the management of the foundation to prepare themselves for the digital era, especially in the field of accounting, so that the foundation's financial reporting becomes transparent and accountable. This activity was attended by 22 participants consisting of Foundation administrators, foster children at the Foundation and PKM committees who are lecturers and students from the Pamulang University Undergraduate Accounting Study Program. This community service (PKM) resulted in the conclusion that Foundation administrators and foster children at the Peduli Tali Bangsa Foundation needed to have knowledge and practice regarding accounting computerization in order to face the digital era so that the Foundation's financial reporting became more comprehensive.